An Examination of Competitive Balance within Interscholastic Football - Johnson, James E; Manwell, Allison K; Scott, Beau F (Journal of Amateur Sport, 2019)
Interscholastic football has the highest participation rates among high school students in the United States. The popularity and nostalgic connection of football is widespread, but competitive balance is often challenged due to differing characteristics of high schools. This study utilized the theory of distributive justice and data from high school athletic associations in all 50 states and District of Columbia to consider which variables (public/private status, school population, rural/urban location, geographical region, and policies) may impact competitive balance at the state-championship level of interscholastic football. The results confirmed that traditionally strong private schools generally located in the Midwest and Northeast win state titles at disproportionately high rates. No other variable was as powerful or significant as the public/private variable. The findings of the study also challenged the effectiveness of existing policies designed to curb private school success. These results can serve pragmatic efforts to ensure competitive balance within interscholastic football.